Dynamic electrical behaviour of a thermoresponsive polymer in well-defined poly(N-isopropylacrylamide)-grafted semiconductor devices. Issue 55 (11th July 2017) - Masuda, Tsukuru; Kajisa, Taira; Akimoto, Aya Mizutani; Fujita, Akane; Nagase, Kenichi; Okano, Teruo; Sakata, Toshiya; Yoshida, Ryo
Abstract : Herein, we found that the phase transition behaviour from swelling state to deswelling state in response to temperature change was electrically detected in real time by using the poly( N -isopropylacrylamide)-grafted gate field effect transistor. Abstract : Herein, a thermoresponsive polymer, poly( N -isopropylacrylamide) (PNIPAAm) was grafted on a Ta2 O5 gate surface by surface-initiated atom transfer radical polymerization. We found that the phase transition behaviour from swelling state to deswelling state in response to temperature change was electrically detected in real time by using the PNIPAAm-grafted gate FET.